Isolation of microsatellite markers in mungbean, Vigna radiata - Kumar, S. V.; Tan, S. G.; Quah, S. C.; Yusoff, K. (Wiley, 2002)
A simple and rapid method for isolating microsatellite loci in mungbean, Vigna radiata,based on the 5′′′′-anchored polymerase chain reaction technique revealed 23 microsatelliteloci and six cryptically simple sequence repeats. We report on the characterization of sevenpolymorphic microsatellite loci in V. radiata. The number of alleles per locus ranged from2 to 5 while the observed heterozygosity ranged from 0 to 0.9048. These markers shouldprove useful as tools for detecting genetic variation in mungbean varieties for germplasmmanagement and crossbreeding purposes.